PENGARUH ANTRIAN HAJI TERHADAP MINAT MELAKSANAKAN IBADAH HAJI DI KABUPATEN MAJENE SULAWESI BARAT (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
The Hajj queue is a consequence of the high number of registrants compared to the available quota, resulting in a long waiting period, even reaching several decades. This phenomenon has psychological and social impacts that may influence the community’s interest in performing Hajj. Therefore, this study aims to analyze the influence of the Hajj queue on the interest of the community in Majene Regency, West Sulawesi, in performing Hajj. This study employs a quantitative method with a causal-comparative (ex post facto) approach. The research population consists of prospective Hajj pilgrims in Majene Regency registered in 2024, totaling 4,440 individuals. A sample of 98 respondents was selected using simple random sampling. Data were collected through a questionnaire and analyzed using simple linear regression. The results indicate that the Hajj queue does not significantly affect the community’s interest in performing Hajj in Majene Regency. Statistical analysis shows that the t-value is smaller than the t-table value (0.163 < 1.985), leading to the acceptance of H₀ and the rejection of Hₐ. These findings suggest that other factors, such as economic conditions and religiosity, may play a more dominant role in determining the interest in performing Hajj.